Does the relationship marketing orientation of an entrepreneur support agency improve performance Evidence from small- and medium-size enterprises in Malaysia - Nor Asiah Omar; Hasnan Md. Aris; Taslima Jannat; Syed Shah Alam; Muhamad Azrin Nazri (PLOS ONE, 2024)
Indexed by WOS/Scopus/ERA